Bacterial Co-Infections and Antibiotic Resistance in Urinary Tract Infection of Covid-19 Patients in Erbil City - Wissam Albeer Nooh; Khadija Khalil Mustafa (Zanco Journal of Pure and Applied Sciences, 2024)
The COVID-19 pandemic has raised concerns over secondary infections because it has limited treatment options and empiric antimicrobial treatment poses serious risks of aggravating antimicrobial resistance. Many studies have shown that COVID-19 patients are predisposed to developing secondary infections. The prevalence of urinary tract infections (UTI) was evaluated in 248 patients admitted to different hospitals in Erbil city, Iraq. Results showed 138 (55.65%) patients were positive for bacterial growth, of which 72 isolates of Gram-negative and 66 isolates of Gram-positive bacteria were isolated and identified from the urine of COVID-19 patients depending on the 16S rRNA gene using PCR. The predominant obtained bacteria were Staphylococci species, of which isolates belong to 6 species, and the predominant Gram-negative species was Pseudomonas spp. which belongs to 4 species. Also, their susceptibility to 15 antibiotics was tested and it was found that most of the Gram-negative isolates were highly resistant to ampicillin 66(91.66%), amoxicillin 60(83.33%), cephalexin 52(72.22%) and cefixime 50(69.44%). While the most effective antibiotic was imipenem, and with percentage of 26(36.11%), it also showed variable sensitivity to other antibiotics. For Gram-positive bacteria, the highest resistance was against cefixime 40(60.60%), ampicillin 28(42.42%), and 18(27.27%) for both amoxicillin and ciprofloxacin, while the most effective antibiotic was gentamicin, which showed effectiveness against all the Gram-positive isolates. Another part of the study concerned with detection of the existence of ESBLs genes responsible for antibiotic resistance. The results revealed that all the isolates possessed the 16S rRNA gene, whereas blaTEM and blaCTX-M were found to be the most possessed genes in all the isolates, with a percentage of (88.33%).